SYNTHESIS, CHARACTERIZATION AND ANTI MICROBIAL ACTIVITY OF NOVEL CHALCONES AND ITS DI HYDRO PYRIMIDINENONES: Pharmaceutical Science-Pharma Chemistry - CH.M.M.PRASADA RAO; D.DHACHINAMOORTHI; M.MOUNIKA; M.PAVANI; SK. SHIREENNAAZ; CH. SRAVANI REDDY; M. SRI ANNAPURNA (International Journal of Life Science and Pharma Research, 2022)
Novel chalcones were synthesized by condensing 1-(2-chlorophenyl) ethanone with aromatic aldehydes derivatives in dilute ethanolic sodium hydroxide solution at room temperature according to Clasein-Schmidt condensation reaction. The synthesized chalcones compounds were reacted with urea and ethanol upon cyclisation gives pyrimidone derivatives .All these compounds were characterized by means of their IR, 1H NMR spectroscopic data and microanalyses. The antimicrobial activity of these compounds was evaluated by the cup plate method.